From lab to field: Innovative RPA‒CRISPR/Cas12a platform for early short-beak and dwarfism syndrome virus nucleic acids detection - Xiuqin Chen; Shizhong Zhang; Su Lin; Meiqing Huang; Shilong Chen; Shao Wang (Poultry Science)
Short beak and dwarfism syndrome virus (SBDSV) is the causative agent of short beak and dwarfism syndrome (SBDS), which is characterized by beak atrophy and dwarfism. SBDS has caused substantial economic losses for waterfowl husbandry industries. To address the urgent need for rapid and accurate SBDSV diagnostics, the study developed a dual-mode detection platform integrating recombinase-aided amplification (RPA) with CRISPR/Cas12a-mediated fluorescence and lateral flow strip readouts. The optimized assay achieved a detection limit of 10 copies/μL. Notably, the platform demonstrated superior specificity to distinguish SBDSV from genetically related Muscovy duck-origin goose parvovirus (GPV) and classical GPV, a distinction unachievable by qPCR. Clinical validation using 36 field samples confirmed 100% concordance with qPCR and indirect immunofluorescence assays, with no cross-reactivity against other common duck pathogens. This innovative detection system provides a robust toolkit for field-deployable SBDSV surveillance and lays a solid foundation for the development of novel diagnostic methodologies applicable to various waterfowl-related pathogens.